Incorporating Inclusive Education Into Translation Studies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the issues of creating a mutually supportive environment for students with special physical and mental abilities in translation studies based on the principles of inclusive education. Translation studies, like other fields, needs to ensure that inclusive education addresses the unique characteristics and needs of each student, as well as providing them with effective and simple ways to teach themselves.